School Tourism Management in Peru: a comparative study in San Pedro Chanel and Carlos Augusto Salaverry - García Trasmonte, Cristina Pamela; Lujan-Vera, Priscila E.; Patiño-García, Lucia-Viviana; Mogollón Taboada, Marlon Martín; Mamani Cornejo, Joyce; Cruz García, Luis Arnaldo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
School tourism constitutes a source of learning to strengthen the cultural identity of students. The objective was to compare the development of school tourism in the educational institutions San Pedro Chanel and Carlos Augusto Salaverry. The Leiper space approach was used. The exhibition was constituted by 200 high school students and 20 teachers. The results show that there is statistically significant differences regarding the knowledge of the tourist resources of the province of Sullana. It was concluded that educational tourism is a strategy that tries to bring the student closer to knowledge, awareness and assessment of tourist resources.